Patients Referred to the Paediatric Cardiology Outpatient Services at Red Cross War Memorial Children's Hospital in 2018: A review of demographics, referral patterns, diagnoses and clinical outcomes - Tlopo, Canicia Puleng (Department of Paediatrics and Child Health, 2023)
Background: Cardiovascular disease (CVD) in children causes considerable morbidity and mortality in Africa and its impact on health systems is an emerging problem. Paediatric cardiology is a highly specialized field based in tertiary centres with worldwide demand exceeding available resources. Upon suspicion of CVD, specialist investigation, early intervention and follow-up are major challenges in low- and middle-income settings. Aim: To investigate and describe patients referred for specialist cardiology services at a tertiary children's hospital in Africa Methods: Red Cross War Memorial Children's Hospital (RCWMCH) is a tertiary paediatric hospital in Cape Town, South Africa. We reviewed patients referred to our outpatient cardiology service, investigating demographics, spectrum of disease, and clinical outcomes. Results: Between 1 January and 31 December 2018, 625 new patients were referred to cardiology outpatient department (COPD) services. Eighty percent (n=501) had structurally normal hearts. The majority of the remainder with confirmed CVD (98%, n=122) had congenital heart defects. Median age of the cohort with CVD was 3.9 months (IQR: 2.6-12.0) with a slight female preponderance (55%). Thirty-four (28%) patients were scheduled for surgery. Ten percent of referred patients had incomplete letters of referral, furthermore we found no feedback plans to these referring practitioners from the COPD doctors. Conclusion: Demands on paediatric cardiology services at RCWMCH are high. Most referred outpatients have structurally normal hearts, straining an already overwhelmed specialist service. However, 28% of patients found to have congenital defects required surgery, highlighting the need to prioritise certain patients. Strengthening communication and feedback channels between cardiologists and generalists will optimise care.